2022
DOI: 10.1101/2022.06.21.22276660
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Pre-Existing Chronic Viral Infection and Reactivation on the Development of Long COVID

Abstract: Epstein-Barr virus (EBV) reactivation has been proposed as a driver of Long COVID (LC), but studies in well-characterized post-acute COVID-19 cohorts of individuals with and without Long COVID symptoms over a time course consistent with current case definitions of LC are limited. In a cohort of 294 hundred adults with a history of SARS-CoV-2 infection, we observed that LC symptoms such as fatigue and neurocognitive dysfunction at a median of 4 months following initial diagnosis were associated with serologica… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…The EBV can reactivate in people with impaired immune systems, as well as when physiological stressors such as an acute infection are present. In previous research, EBV reactivation was shown to occur during acute SARS-CoV-2 infection as indicated by the presence of detectable circulating EBV DNA or viral capsid antigen (VCA) IgM-positive [ 17 ]. In the current work, through meta-analysis, we have shown that EBV reactivation in COVID-19 patients increased the mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The EBV can reactivate in people with impaired immune systems, as well as when physiological stressors such as an acute infection are present. In previous research, EBV reactivation was shown to occur during acute SARS-CoV-2 infection as indicated by the presence of detectable circulating EBV DNA or viral capsid antigen (VCA) IgM-positive [ 17 ]. In the current work, through meta-analysis, we have shown that EBV reactivation in COVID-19 patients increased the mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Latency is the outcome of virus host adaptation, in which herpesvirus genomes are maintained in a non-replicative state, hidden from the host’s immune response. Changes in the host’s immune status can result in a failure of the host to suppress herpesvirus replication with consequent disease manifestations [ 45 , 60 , 61 ]. Infection by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) can have several clinical outcomes depending upon the host’s immunological response to infection [ 62 ], and treatments for COVID-19 can also be immunosuppressive.…”
Section: Discussionmentioning
confidence: 99%
“…B-cell changes during PASC have also been described, including increases in activated (CD86 hi HLA-DR hi ) and double negative (IgD -/CD27 -/CD24 -/CD38 -) subsets. In addition, such B cell change is positively associated with high anti-spike antibody responses (indicating the persistent spike antigen) and responses against non-SARS-CoV2 antigens (indicating the reactivation of latent herpesvirus infections, such as Epstein-Barr Virus (EBV)) (17,84).…”
Section: B Cellsmentioning
confidence: 99%
“…We examine potential factors contributing to tissue injury to look for common features among otherwise highly variable clinical presentations of PASC (Figure 1). The mechanistic contributions of comorbid conditions to PASC are not addressed here, although links between PASC symptoms, such as fatigue and neurocognitive function, have been previously associated with Epstein Barr Virus (EBV) reactivation and HIV co-infection, respectively (17). We also do not address specific conditions (i.e., obesity, diabetes, and aging-associated disorders) that may be linked to COVID-19 severity and the development of PASC.…”
Section: Introductionmentioning
confidence: 99%